71 Establishment of an assay for the determination of ADA2 activity. (15th December 2021) - Davis, Mark; Ralph, Elizabeth; Gilmour, Kimberly; Buckland, Matthew
Abstract : ADA2 deficiency (DADA2) presents, in the most severe instances, before the age of 10 with recurrent strokes or cerebral haemorrhage, patients have also been described as presenting with joint pains, hepatomegaly, splenomegaly and gastrointestinal problems. It is thought that, over time, upregulation of proinflammatory cytokines in these patients causes organ damage. The reduced ADA2 enzyme activity is caused by an autosomal recessive mutation in the CECR1 gene. There is currently no assay available to determine ADA2 activity to support the diagnosis of DADA2. We have evaluated a commercial ADA activity assay, adapting it for use in detecting ADA2 enzyme activity, by using a commercial ADA1 inhibitor. The assay is based on enzymic detection which results in the production of a coloured dye, measurable at 550nm. Incubating patient serum in the presence of kit reagents and the ADA1 inhibitor, at 37°C, the samples absorbance is measured in a kinetic manner and a determination of enzyme activity derived. Through our evaluation we have established a normal range for ADA2 activity and have measured ADA2 activity in patients suspected of having DADA2. All patient samples that were found to have an absent or reduced ADA2 activity have been shown to have abnormal CECR1 genetics. As part of the evaluation, several samples that showed normal ADA2 activity, have also been evaluated for CERC1 genetics, and all were found to be normal. Although continued evaluation is needed, the assay shows good correlation with genetic analysis and shows promise as a reliable assay for the detection of DADA2. We hope to offer the assay as part of our clinical service in the Immunology lab at GOSH, with the test being available to patients across the country. This should reduce the time and cost required for diagnosis of DADA2 compared to genetics and improve care for patients.